A Project Proposal of Leftover Rice Starch as an Effective Component for Ideal Biodegradable Plastic: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Plastics have become one of the most utilized materials in recent years. As time passes, plastics are used across almost every sector of human life, including product packaging, containers, appliances, and even in building and construction. Rice is a grass frequently farmed for its seed and is best known as a worldwide staple meal. It is derived from wheat. Cooked Rice can convert into resistant starch since it contains starchy calories that it can't simply break down and is a renewable supply. This study is conducted to produce bioplastics from leftover rice starch. Using bioplastics to replace some of the inorganic plastics can be a solution to solve global warming and reduce pollution.  The researcher design used for the study was quantitative experimental research while utilizing purposive sampling techniques. The statistical treatment used for this study was frequency and percentage, weighted mean, and t-test to determine the difference between the two groups of respondents. Using the questionnaire as the research instrument, the researchers surveyed to identify the bioplastic's effectiveness in terms of materials, procedures, durability and presentation. The study's respondents are 5 STEM Teachers and 5 Environmental Engineers. The study results regarding materials, procedure, durability and presentation are highly acceptable. The overall weighted mean of the STEM Teachers was 4.04, interpreted as Highly Acceptable, and Environmental Engineers had an overall weighted mean of 3.71, interpreted as Highly Acceptable. The t-computed was -0.083130, and the t-critical was 2.447. It indicates no significant difference between the assessments of the two groups of respondents. For the further progress of the project, the respondents recommended that the researchers present a larger piece of the product to assess. Also, look for another alternative ingredient for glycerin and ensure that all materials needed are inside the house, for that will be helpful to future researchers.
Keywords: biodegradable plastic; plastic; rice starch